2018
DOI: 10.3340/jkns.2017.0188
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Insufficiency Fractures : How to Classify?

Abstract: ObjectiveThe diagnosis of insufficiency fractures of the sacrum in an elder population increases annually. Fractures show very different morphology. We aimed to classify sacral insufficiency fractures according to the position of cortical break and possible need for intervention.MethodsBetween January 1, 2008 and December 31, 2014, all patients with a proven fracture of the sacrum following a low-energy or an even unnoticed trauma were prospectively registered : 117 females and 13 males. All patients had a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…When the results of bone mineral densitometry (BMD) that was measured by dualenergy X-ray absorptiometry method were evaluated, the mean value was found to be -3.62 ±0.46 (mean ± SD). According to the classification system of Bakker et al (7) of SIFs, the most common fracture type was B1. Numerical and percentage distribution of fracture types are shown in Graphic 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the results of bone mineral densitometry (BMD) that was measured by dualenergy X-ray absorptiometry method were evaluated, the mean value was found to be -3.62 ±0.46 (mean ± SD). According to the classification system of Bakker et al (7) of SIFs, the most common fracture type was B1. Numerical and percentage distribution of fracture types are shown in Graphic 2.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1. Classification of sacral insufficiency fractures according to Bakker et al (7) Type A: Fractures of the sacral ala…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IF is more common in the elderly, and less common in men than women. Recently, Bakker et al [6] published a study about the diagnose of Sacral IF for 130 patients, who aged between 46 and 98 years (mean, 79.8 years), with 117 females and 13 males. Melton et al [7] analyzed the contribution of gender on the incidence of pelvic insufficiency fractures in a retrospective review of a Mayo Medical database, of which total of 198 patients with 204 fractures, showed the incidence of pelvic insufficiency fractures was nearly twice as common in women (47.5/100000) as it is in men (24.4/100000).…”
Section: Discussionmentioning
confidence: 99%